Enhancement of flavonoid production by suppressing cinnamate-4-hydroxylase (C4H) gene expression using RNA and CRISPR interference systems in Nicotiana tabacum and Boesenbergia rotunda cell suspension cultures / Karlson Chou Khai Soong - Karlson Chou , Khai Soong (2022)
Flavonoids are an important natural compound in plants with many health benefits, including antioxidant, anticancer, antiviral, and anti-inflammatory properties. However, the scarcity of flavonoid chemicals in nature restricts their industrial applicability. Cinnamate-4-hydroxylase (C4H) is a critical enzyme found at the very first branching point in the flavonoid biosynthetic pathway. By silencing the branching pathway, the redirection of the metabolic flux may enhance the desired flavonoid production in plants. This study demonstrated how C4H silencing affects flavonoid production in Nicotiana tabacum cell suspension cultures using RNAi and CRISPRi silencing systems. The main aim of this study was to enhance the flavonoid production by silencing its C4H using (1) RNAi system with a partial cDNA of C4H from Boesenbergia rotunda (designated as BrC4H) and (2) CRISPRi system with guide RNAs (gRNAs) targeting the promoter region of endogenous C4H. Prior to plant transformation, the previously constructed partial pANDA-BrC4H plasmid containing BrC4H cDNA (1,302 kb) was verified by PCR analysis and sequencing. To construct the CRISPRi vector, guide RNAs (gRNAs) targeting the region at the C4H’s promoter were designed and cloned into a CRISPRi vector. Both vectors were introduced separately into the established B. rotunda and N. tabacum cell suspension cultures through Agrobacterium-mediated transformation. About 76.2 % and 52.9 % N. tabacum cell suspension cultures transformed with CRISPRi and RNAi vectors, respectively, survived under hygromycin selection media. In contrast, 9.2 % of the B. rotunda cell suspension cultures survived after transforming with an RNAi vector. Attempts to transform B. rotunda cell suspension cultures with the CRISPRi vector was unsuccessful as all cells were dead because of the nationwide lockdown due to the pandemic. All transformants that survived on antibiotic media were harvested for PCR analysis. The PCR-positive cell lines were maintained for another three months before being harvested for quantitative-real-time PCR (qPCR) analysis. The expression of C4H for RNAi- and CRISPRi-silenced N. tabacum cell suspension cultures was 0.75- and 0.44-fold, respectively, lower than wild type. However, for other flavonoid-related genes, such as 4CL and CHS, the C4H-silenced cells using CRISPRi showed a higher expression than RNAi-silenced and wild type. Similarly, the accumulation of flavonoids, namely pinostrobin, naringenin, and chlorogenic acid, in the CRISPRi-silenced cells was higher than in RNAi-silenced and wild type. These findings showed that the flavonoid biosynthesis has altered after silencing the C4H via RNAi and CRISPRi, thus increasing several targeted flavonoids.